2010
DOI: 10.1007/s10339-010-0374-8
|View full text |Cite
|
Sign up to set email alerts
|

West vs. West like East vs. West? A comparison between Italian and US American context sensitivity and Fear of Isolation

Abstract: Easterners tend to process information more holistically than Westerners. Kim and Markman (J Exp Soc Psychol 42(3):350-364, 2006) suggest that these differences are rooted in higher chronic levels of Fear of Isolation (FOI) for those cultures that process information more holistically. The goal of this study was to determine if these differences and their suggested cause could be found with two different Western cultures. Testing Italian (IT) and US American (US) adults, we found that IT participants processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 17 publications
(55 reference statements)
12
14
1
Order By: Relevance
“…In a previ ous research, we found analogous results demonstrating that Italians have a higher chronic level of foi than us American participants (Federici et al, culture difference in the chronic psychosocial factor of Fear of Isolation. In that research, we also demonstrated that Italian participants processed information more holistically and were therefore more similar to Koreans and Japanese participants (Masuda and Nisbett, 2001; than to us Americans Federici et al, 2011). Finally, in that research we replicated previous research demon strating that the priming of f o i caused participants to pay more attention to the overall context with us Americans, but we also discovered that Italians were more likely to process information holistically following the priming of f o i than us Americans.…”
Section: Our Study: Chronic Social Factor's ( F O I ) Influence On Cosupporting
confidence: 80%
See 4 more Smart Citations
“…In a previ ous research, we found analogous results demonstrating that Italians have a higher chronic level of foi than us American participants (Federici et al, culture difference in the chronic psychosocial factor of Fear of Isolation. In that research, we also demonstrated that Italian participants processed information more holistically and were therefore more similar to Koreans and Japanese participants (Masuda and Nisbett, 2001; than to us Americans Federici et al, 2011). Finally, in that research we replicated previous research demon strating that the priming of f o i caused participants to pay more attention to the overall context with us Americans, but we also discovered that Italians were more likely to process information holistically following the priming of f o i than us Americans.…”
Section: Our Study: Chronic Social Factor's ( F O I ) Influence On Cosupporting
confidence: 80%
“…We, therefore, explore whether differences in manipulated f o i for Italian, us Americans, and Chinese influence context sensitivity similar/parallel to previous research (Masuda and Nisbett, 2001;Federici et al, 2011).…”
Section: Our Study: Chronic Social Factor's ( F O I ) Influence On Comentioning
confidence: 80%
See 3 more Smart Citations